Recovery of metal and energy from capacitive deionization (CDI) discharged brine - Miah, Md. Sazal; Bora, Tanujjal; Chanchana Thanachayanont; Ricco, Raffaele; His Majesty the King{u2019}s Scholarships (Thailand) (Pathum Thani : Asian Institute of Technology, 2022)
Activated carbon cloth (ACC) electrodes modified with manganese dioxide (MnO2) are used in capacitive deionization (CDI), a promising strategy for conducting metal and energy recovery along with desalination. The removal capability of copper (Cu2+), Nickel (Ni2+), and Chromium (Cr2+) ions and their recovery in the metallic form are examined. Multiple important concerns have been investigated to test the feasibility of CDI metal recovery from a practical point of view, like the impact of the voltage on the ion adsorption, metal recovery, the concentration of metal ions, and its long-term viability. During the charging step of the CDI cell, some energy is stored in the carbon electrode, and this energy can be further recovered during the discharging phase. In this thesis, an energy recovery mechanism is developed and investigated to recover the energy during the desorption step by utilizing a four-switch buck-boost converter as a DC/DC converter and a supercapacitor (SC) as the energy storage device. A basic CDI cell is constructed to perform the above experiments. Faraday's laws of electrolysis and atomic absorption spectroscopy (AAS) analysis are performed to understand the Cu2+ and Cr3+ deposition efficiency during metal recovery in the form of electroplating, and to find out the appropriate voltage and pH range. Lastly, energy recovery efficiency analysis is performed to assess the amount of energy that can actually be recovered from the CDI cell.
Thesis (M. Eng.) - Asian Institute of Technology, 2022
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Nanotechnology
Keywords: Heavy metals -- Environmental aspects; Energy transfer